2017
DOI: 10.18520/cs/v112/i05/1012-1015
|View full text |Cite
|
Sign up to set email alerts
|

Excellence and Diversity Mapping of Research in IISc, IITs, NUS and NTU

Abstract: A three-dimensional evaluation approach is used to decompose the research performance of the two leading research clusters from India and Singapore into three components -size, excellence, and balance or evenness. Data are retrieved from the Excellence Mapping web application. The NUS + NTU cluster from Singapore outperforms the IISc + 7IITs cluster from India on all three counts. Keywords: Balance, bibliometrics, excellence, research evaluation, size.A benchmarking exercise on the research performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is representative of the distribution observed in higher educational institutes in India. (Prathap 2017;Chanana 2006) have reported on the marginalized representation of females in teaching and lead-ership profiles in Indian Higher Education institutions and in fact a recent survey 21 from the year 2019-20 amongst Institutes of National Importance in India shows that females occupy only 20% of the teaching positions. Similarly, it has been observed that only 21% of the lecturers in higher education institutes belong to the reserved caste category.…”
Section: Dataset Annotationmentioning
confidence: 99%
“…This is representative of the distribution observed in higher educational institutes in India. (Prathap 2017;Chanana 2006) have reported on the marginalized representation of females in teaching and lead-ership profiles in Indian Higher Education institutions and in fact a recent survey 21 from the year 2019-20 amongst Institutes of National Importance in India shows that females occupy only 20% of the teaching positions. Similarly, it has been observed that only 21% of the lecturers in higher education institutes belong to the reserved caste category.…”
Section: Dataset Annotationmentioning
confidence: 99%